Efeito do solvente em propriedades eletrônicas de compostos mesoiônicos usando o método QM/MM sequencial - Moreira, Emerson Gonçalves (2019)
The mesoionic compounds present a very curious chemical structure and exhibit a range of applications in various fields. There are several theoretical and experimental studies with the mesoionic ones, however, there is a shortage of works on its properties in solvent environment. In this work, the solvent effect was investigated through the continuous and discrete solvation models of two types of rings: 1,3,4-thiazolium-2-thione (NNSS) and 2,3-tetrazolium-5-thione (NNNNS ). The discrete method was employed interactively using the sequential Molecular Mechanics / Quantum Mechanics (S-QM / MM) method to obtain the effect of the polarization of the solvent molecules against the solvents used. The DFT Functional Theory and TimeDependent DFT (TD-DFT) were used in calculations of optimization of geometry and electronic properties of the monomers and dimers of mesoionics. The results showed that the solvent effect did not produce significant changes in the bonding lengths and angle for the two rings investigated. The mesoionic complexes are favored in antiparallel orientations and in the presence of aromatic groups, allowing interactions between the mesoionic dipoles. In protic polar media, the formation of solute-solvent bonds occurs in greater amount in the exocyclic sulfur because of its position and the charge of this site. The evaluation of the absorption spectra revealed the presence of two main bands n → π∗and π → π∗. The inclusion of the solvent effect results in solvatocromic shifts to regions of higher energy (blueshift). The values for the electronic transitions are in agreement with the results found in the literature.